Горизонтальные изменения сообществ фитопланктона Павловского водохранилища (Республика Башкортостан, Россия) - Шкундина, Ф.Б.; Полева, А.О. (Альгология, 2014)
Застосовано деякі підходи еколого-флористичної класифікації для виявлення індикаторних видів, використаних в подальшому для оцінки екологічного стану фітопланктону в Павлівському водосховищі. Виділено види, розповсюджені по всій території водосховища: Chlorella vilgaris Beij. та Aphanocapsa inserta (Lemmerm.) Cronberg & Komárek, а також види, характерні для різних створів. Диференційовано 4 угруповання фітопланктону з 2 варіантами одного з них. Склад угруповань відображає зміни ступеня евтрофування на різних створах. We used some of the approaches of ecological-floristic classification for the identification of indicator species. The indicator species are used then to assess the environmental conditions in Pavlovskoe Reservoir. 155 species and intraspecific taxa of Algae and Cyanoprokaryotes from 90 genera, 50 families, 25 orders, 10 classes and 7 divisions had been determined by the authors during the research in 2003, 2008 and 2009 years. Allocated species, which are widespread throughout the territory of the reservoir – Chlorella vulgaris and Aphanocapsa inserta, and species typical for different sites. Also it was differentiated 4 autotrophic plankton community, with two versions of one of them. The composition of communities reflects the changes in the degree of eutrophication of the reservoir.